2011
DOI: 10.1007/978-3-642-21726-5_17
|View full text |Cite
|
Sign up to set email alerts
|

Designing Shared Public Display Networks – Implications from Today’s Paper-Based Notice Areas

Abstract: Abstract. Large public displays have become a regular conceptual element in many shops and businesses, where they advertise products or highlight upcoming events. In our work, we are interested in exploring how these isolated display solutions can be interconnected to form a single large network of public displays, thus supporting novel forms of sharing access to display real estate. In order to explore the feasibility of this vision, we investigated today's practices surrounding shared notice areas, i.e. plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 16 publications
7
52
0
Order By: Relevance
“…Previous work has identified the following reasons [3]: on one hand, PNAs have a strong local character, often addressing certain communities only. By contrast, web-based platforms allow a large number of people to be reached, even at a distance.…”
Section: Interaction Techniques For Pnasmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work has identified the following reasons [3]: on one hand, PNAs have a strong local character, often addressing certain communities only. By contrast, web-based platforms allow a large number of people to be reached, even at a distance.…”
Section: Interaction Techniques For Pnasmentioning
confidence: 99%
“…To include all interaction techniques 3 , each task combined a set of three techniques (one each for creating, posting, and retrieving content). We used a within-subject design.…”
Section: Tasksmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on observation of bulletin boards in three local areas in California and interviews with residents, Churchill et al [10] concluded that bulletin boards serve as a communication media to seek and advertise (1) viewpoints, (2) activities, (3) events and (4) services. In another observational study, Alt et al [4] determined that there is an interplay among a bulletin board's location, its stakeholders (the manager, the content providers and the viewers) and its content. Content that has no relation to the location is rarely posted.…”
Section: Public Displaysmentioning
confidence: 99%
“…For example, Alt et al's Digifieds [2] provide a digital version of a more traditional paper based public notice areas [3]. Their system allows posting and viewing of classifieds on a public display network, while at the same time preserving locality and local nature of postings.…”
Section: Related Workmentioning
confidence: 99%